Tinjauan Bentuk Persahabatan dalam Komunitas Calon Imam Menurut Pandangan Plato - Bonaventura Anggoro Bramastyo Aji (Parahyangan Catholic University, 2020)
The community becomes a place for candidates of priest to socialize and get their affective needs. If needs are met, the candidates of priest can build friendly relationships. However, there are many forms of friendship. With the help of Plato’s ideas, this paper tries to find the right form of friendship to be developed in the community of candidates of priest.